MANAGEMENT OF ENTERPRISE SUSTAINABLE DEVELOPMENT IN THE CONDITIONS OF A CHANGING ENVIRONMENT - NEMASHKALO, Karina; KHAKHALIEV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The need to solve the global problems of humanity has already convincingly and indisputably proven the feasibility of introducing the concept of sustainable development into the practical sphere of economic activity and management of business entities. However, the complexity and scale of the components of the trilemma of sustainable development create several risks and threats to the organization's management system. These risks are exacerbated by the unpredictable effects of external and internal business environment factors. The article examines the peculiarities of managing the activities of enterprises based on sustainable development under the influence of factors of a changing business environment. The proposed author's vision of the content of sustainable development is based on the combination of commercial and non-commercial goals of the company's existence. The implementation of the principles of the global concept of sustainable development in the practical sphere of enterprise management showed the urgent need to consider the challenges and risks exacerbated by the high degree of volatility and variability of the external business environment. Under such conditions, modern approaches to management are updated, which are based on the principles of risk management and allow effective management and leveling of the consequences of transformational transformations associated with the sustainable development of the company. It was determined that the key risks for sustainable business are environmental, social and managerial risks. Considering the nature of their origin and the nature of the manifestation, the article examines the phasing of the risk management process recommended by the world's leading companies when the company achieves the goals of sustainable development.A set of management methods based on the principles of sustainable business development is recommended under the conditions of the need to level the risks of the organization's changing environment. Among the main ones, the following are proposed: a method of analyzing hierarchy processes; method of analytical and network processes; a method of assessing the priority of organizational sub-risks of sustainable management; compliance, assessment of codes of business conduct, assessment of sustainability risks of supply chains.It was determined that the achievement of the goals and objectives of sustainable development and modern approaches to risk management of the business environment should be based on a more transparent disclosure of information about activities. The international standard IFRS S1 "General Requirements For Disclosures Of Sustainability-Related Financial Information" is not just a strategic guideline, but a necessity for the disclosure of information and the creation of a transparent information and analytical management base. This practice is now becoming mandatory for large and medium-sized businesses in foreign management practice, underlining its importance in sustainable business management.
Keywords: sustainable development; company; business; management; risks; business environment